Emotion perception bias associated with the hijab in Austrian and Turkish participants. Issue 5 (May 2022) - Korb, Sebastian; Deniz, Tugba Ceren; Ünal, Bengi; Clarke, Alasdair; Silani, Giorgia
In a cross-cultural study, we investigated the link between explicit attitudes towards the hijab and implicit measures of cultural and religious bias during the recognition of emotions. Participants tested in Austria ( N = 71) and in Turkey ( N = 70) reported their attitude towards the hijab, and categorised in a mousetracker task happy and sad faces of women, shown with five levels of intensity, and framed either by a hijab or by an oval-shaped mask. The two samples did not differ in their explicit attitudes towards the hijab. However, negative attitude towards the hijab predicted greater sadness attribution to happy faces with the hijab in Austrian participants. Unrelated to their explicit attitudes, Turkish participants attributed more sadness to happy faces with than without the hijab. Results suggest that the sight of the hijab activated, in both Austrian and Turkish participants, implicit biases resulting in associations with sadness and negative emotions.